Some Studies on Correlation of Crown Projection Area and Bole Diameter in Sal (Shorea robusta) as an Aid in Thinning - Suri, S. K. (Indian Forester, 1970)
Thinning is a function of numbers and the numbers left at different stages (regime) determine the development of the crop. From the correlation studies between diameter at breast height and crown projection area of Shorea robusta (sal), author describes a method by which the basic knowledge of number of trees per acre in a fully stocked crop at different diameters can be known and therefrom optimum growing space required by trees determined. This is, however, a preliminary study and further work is necessary.